MAGNETIC SOLID PHASE EXTRACTION APPLICATIONS COMBINED WITH ANALYTICAL METHODS FOR DETERMINATION OF DRUGS IN DIFFERENT MATRICES REVIEW - Kepekci Tekkeli, Şerife Evrim; Durmus, Zehra (Journal of the Chilean Chemical Society, 2019)
Sample preparation procedures are essential for drug analysis in biological fluids, tissues, pharmaceutical preparations, food and environmental matrices. For this purpose different techniques have been used like protein precipitation, liquid liquid extraction (LLE) and solid phase extraction (SPE). Magnetic solid phase extraction (MSPE) has become a highly preferred method due to its advantages as a sample preparation-pretreatment technique when compared to classical methods as a novel type of SPE. Basically, this type of extraction is based on the separation of different analytes from complex matrices based on the use of magnetic nanoparticles (MNPs) as adsorbents. Magnetic solid phase extraction minimizes the use of additional steps which reduces the manipulation of conventional extractions. The main advantages depend on its simplicity, environmentally friendly process, disposable cost, reduced solvent consumption, and short duration. In this review, special attention is paid on drug analysis by using MSPE prior to various analytical methods from biological, environmental and food matrices. MSPE applications, with various types of magnetic adsorbents, and different analytical method combinations were revealed for drug analysis. Abbrevıatıons: LLE, liquid liquid extraction; SPE, solid phase extraction; MSPE, magnetic solid phase extraction; DLLME, dispersive liquid-liquid microextraction; SBSE, stir bar sorptive extraction; SPME, solid phase microextraction; SFE, supercritical fluid extraction; PFE, pressurized fluid extraction; MAE, microwave-assisted extraction; MSPD, matrix solid-phase dispersion; MNP, magnetic nanoparticle; SPION, superparamagnetic iron oxide nanoparticles; MRI, magnetic resonance imaging; CE, capillary electrophoresis; UV-Vis, ultraviolet-visible; MS, mass spectrometric; PEI, polyethyleneimine; PVA, polyvinylalcohol; PEG, polyethyleneglycol; PVP, polyvinylpyrrolidone; LC, liquid chromatography; GC, gas chromatography; HPLC, high performance liquid chromatography; FLD, fluorimetric detection; CZE, capillary zone electrophoresis; poly(MAA-co-EDMA), poly methacrylic acid co-ethyleneglycol dimethacrylate LOD, limits of detection; LOQ, limit of quantification; SDS, sodium dodecylsulfate; MPTS, 3-methacryloxypropyl trimethoxysilane; CTAB, cetyltrimethylammonium bromide; MWCNTs, multiwalled carbon nanotubes; DBMNPs, diatomite bonding Fe3O4 magnetic nanoparticles; EGDMA, ethylene glycol dimethacrylate; DCBI, desorption corona beam ionization; MNGO, magnetic nano graphene oxide; NSAIDs, nonsteroidal anti-inflammatory drugs; UAMDSPME, ultrasound-assisted magnetic dispersive solid-phase microextraction; MRLs, maximum residue limits; SA, sulfonamide; PCL, polycaprolactone; MM-PCL-SPE, microspheres solid-phase extraction; MISPE, molecularly imprinted solid-phase extraction; DMIP, dual-template molecularly imprinted polymer; MOF, metal-organic framework; ZIF-8, zeolite imidazolate framework-8; MSPDE, magnetic solid phase dispersion extraction; MIMM, molecularly imprinted magnetic microsphere.